Pendidikan Karakter pada Anak Usia Dini di TK Setyo Budi PGRI Podoluhur Kecamatan Klirong Kabupaten Kebumen - Zahro, Fatimatuzzahro; Adib, Shohibul; Hargina, Devi Yaniar Wi (Prodi Pendidikan Agama Islam IAINU Kebumen, 2022)
The importance of character education should be applied since early childhood, because at that age is the golden age or the golden age (0-6 years) where in this period children will absorb any information from the surrounding environment. The aims of this research are: (1)To find out character education in early childhood in Setyo Budi Kindergarten, PGRI, Podoluhur Village. (2)To find out the impact of character education on early childhood in Setyo Budi PGRI Kindergarten, Podoluhur Village. This type of research is a qualitative engineering research. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation, data verification and drawing conclusions.Based on the results of the research conducted, it was found that: (1) character education has been carried out for early childhood in Setyo Budi PGRI Kindergarten, namely discipline, giving advice, practicing responsibility, exemplary, and using Javanese language. (2) the impact that occurs can be seen from the attitudes carried out on students including: getting used to saying greetings, being disciplined in coming on time,getting used to saying sorry, please, thank you, being responsible for mistakes made, having good manners, and having good manners. high mutualrespect.